The Impact of Agile Development Strategies on Team Productivity in Full Stack Development Projects - Harshita Cherukuri (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Agile development methodologies have gained significant popularity in recent years, particularly in the field of full stack software development. These strategies aim to enhance team collaboration, adaptability, and productivity. This research paper investigates the impact of agile development strategies on team productivity in full stack development projects. Through a combination of qualitative and quantitative data analysis, including surveys, interviews, and case studies, we explore how agile practices such as Scrum, Kanban, and Extreme Programming (XP) influence team dynamics, communication, and overall productivity. The findings suggest that agile methodologies, when properly implemented, can lead to improved team productivity, faster time-to-market, and higher customer satisfaction. However, the success of agile adoption depends on factors such as team size, project complexity, and organizational culture. This paper provides valuable insights for software development teams and organizations considering the implementation of agile strategies in their full stack development projects.